Calidad de vida en pacientes con cuidados paliativos de la Casa de Enfermos Terminales Fundación Liga de Caridad de Loja - Quezada Ordoñez, Isabel Maripaz (2024)
Palliative care focuses on improving the quality of life of the human being, trying to cover physical, psychological, social, emotional and spiritual needs. According to the World Health Organization (WHO), around 40 million people require palliative care, only 14% of whom receive it. In Latin America, the deficit is even greater, covering less than 1% of the population. The aim of the research was to evaluate the quality of life of palliative care patients at the House for the Terminally Ill Foundation League of Charity of Loja in the period October 2022-March 2023. It was configured as a quantitative, crosssectional cohort research study, made up of 16 participants who met the inclusion and exclusion criteria and who were administered the EORTC QLQ C15 PAL test and a family satisfaction survey, of which 37.50% (n=6) belong to the age range 81-90 years, 68.75% (n=11) are women, 43.75% (n=7) are single, and 56.25% (n=9) are under the care of their children, who have a monthly income of approximately 2 minimum living wages. In terms of quality of life, 68.75% (n=11) perceive their quality of life as fair, and 6.25% (n=1) as very poor, while 100% (n=16) of the families were satisfied with the care they receive from the institution. It was concluded that palliative care has a positive influence both psychologically and physically on the quality of life of the residents